DNA assisted synthesis of CeO2 nanocrystals with enhanced peroxidase-like activity. Issue 29 (11th July 2018) - Wang, Meng; Wang, Mei-Fang; Wang, Yi-Ming; Shen, Ji-Wei; Wang, Zhi-Ying; Gao, Han; Wang, Li-Li; Ouyang, Xiangyuan
Abstract : We have synthesized a series of CeO2 nanocrystals in different sizes with DNA as the template by a hydrothermal synthesis method. Abstract : A series of CeO2 nanocrystals with different sizes have been synthesized with DNA as the template by a hydrothermal synthesis method. The peroxidase-like activity of the CeO2 nanocrystals was found to be strongly enhanced by DNA doping.